2011
DOI: 10.1002/cncr.26453
|View full text |Cite
|
Sign up to set email alerts
|

Smoking negatively impacts renal cell carcinoma overall and cancer‐specific survival

Abstract: BACKGROUND: Tobacco use is a leading cause of premature death, yet few studies have investigated the effect of tobacco exposure on the outcome of patients with renal cell carcinoma (RCC). The authors of this report retrospectively studied the impact of smoking on clinicopathologic factors, survival outcomes, and p53 expression status in a large cohort of patients with RCC. METHODS: Eight hundred-two patients (457 nonsmokers and 345 smokers) who had up to 232 months of follow-up were compared for differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 34 publications
1
37
1
Order By: Relevance
“…Smoking was also identified as an indicator of poor prognosis in patients with oropharyngeal cancer, regardless of the tumor p16 status or treatment (7). In addition, patients with renal cell carcinoma and a history of smoking were more likely to have advanced pathologic features and poorer survival outcomes (4). Similar significant associations between smoking and poorer disease-free survival and time to recurrence have also been observed in patients with colon cancer (3).…”
Section: Discussionmentioning
confidence: 73%
“…Smoking was also identified as an indicator of poor prognosis in patients with oropharyngeal cancer, regardless of the tumor p16 status or treatment (7). In addition, patients with renal cell carcinoma and a history of smoking were more likely to have advanced pathologic features and poorer survival outcomes (4). Similar significant associations between smoking and poorer disease-free survival and time to recurrence have also been observed in patients with colon cancer (3).…”
Section: Discussionmentioning
confidence: 73%
“…The effect of smoking may be mediated through inflammation, oxidative tissue damage, or immune suppression that acts on cancer progression [9,11]. Smoking-induced activated macrophages may generate reactive oxygen species that promote angiogenesis, tumor invasion, and metastasis [9,13]. Tobacco exposure also can alter multiple immunologic functions, including the innate and adaptive immune system [9].…”
Section: Discussionmentioning
confidence: 99%
“…14 Many studies have examined the relationship between smoking and mortality among cancer patients. A history of ever smoking compared with never smoking was associated with an increase in overall mortality [15][16][17][18][19][20][21][22][23] and cancer-specific mortality. 15,16,24 However, other studies fail to show a significant difference in mortality based on smoking status after controlling for covariates.…”
Section: Introductionmentioning
confidence: 99%
“…A history of ever smoking compared with never smoking was associated with an increase in overall mortality [15][16][17][18][19][20][21][22][23] and cancer-specific mortality. 15,16,24 However, other studies fail to show a significant difference in mortality based on smoking status after controlling for covariates. [25][26][27][28] In the head and neck cancer literature, smoking significantly increases overall mortality and cancer-specific mortality, 10,21,23,[29][30][31][32][33][34] and pack-years of smoking has a dose-response positive relationship with mortality, 23,30,35 yet some studies reported nonsignificant differences in overall mortality [36][37][38][39] and cancer-specific mortality 37,40 between smokers and nonsmokers.…”
Section: Introductionmentioning
confidence: 99%